2013
DOI: 10.1111/bph.12349
|View full text |Cite
|
Sign up to set email alerts
|

Increased LDOPA‐derived dopamine following selective MAOA or ‐B inhibition in rat striatum depleted of dopaminergic and serotonergic innervation

Abstract: Selective MAO type B (MAO-B) inhibitors are effective in potentiation of the clinical effect of L-DOPA in Parkinson's disease, but dopamine (DA) is deaminated mainly by MAO type A (MAO-A) in rat brain. We sought to clarify the roles of MAO-A and MAO-B in deamination of DA formed from exogenous L-DOPA in rat striatum depleted of dopaminergic, or both dopaminergic and serotonergic innervations. We also studied the effect of organic cation transporter-3 (OCT-3) inhibition by decinium-22 on extracellular DA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 49 publications
4
27
0
1
Order By: Relevance
“…SC18396; Santa Cruz Biotechnology, USA). The MAOA antibody co-localizes with the TPH antibody in dorsal raphe neurons in our mouse brain sections in a similar pattern to locus coerulius neurons that are double labeled with TPH antibodies and the same MAO-A antibody as used in the present study (Sader-Mazbar et al, 2013). …”
Section: Methodssupporting
confidence: 70%
“…SC18396; Santa Cruz Biotechnology, USA). The MAOA antibody co-localizes with the TPH antibody in dorsal raphe neurons in our mouse brain sections in a similar pattern to locus coerulius neurons that are double labeled with TPH antibodies and the same MAO-A antibody as used in the present study (Sader-Mazbar et al, 2013). …”
Section: Methodssupporting
confidence: 70%
“…Humans lacking MAO B have greatly elevated levels of phenylethylamine (Murphy et al, 1990). In rats, numerous microdialysis experiments have been conducted to measure amine changes in different disease models (including addiction) or to assess the effects of MAO inhibitors (for example, (Butcher et al, 1990, Lamensdorf et al, 1996, Bazzu et al, 2013, Sader-Mazbar et al, 2013, Bolea et al, 2014). After treatment with MAO inhibitor, mice showed significantly higher noradrenaline and serotonin levels and significantly lower metabolites (including DOPAC from dopamine) (Lum and Stahl, 2012).…”
Section: Mao Influences the Monoamine Levels In Brainmentioning
confidence: 99%
“…However, MAO selectivity is quite poor since, for example, MAO B also decomposes serotonin only five times slower than dopamine [89]. On the other hand, experiments have demonstrated that striatal dopamine tissue levels or extracellular levels are increased by the inhibition of MAO A with clorgyline [90][91][92]. In the human brain, MAO A exists in catecholaminergic neurons, but MAO B is found in serotonergic neurons and glial cells [93].…”
Section: Hydrogen Peroxide-related Enzymesmentioning
confidence: 99%